Clinical application of transcranial magnetic stimulation in multiple sclerosis - Zhou, Xiaoliang; Li, Kailin; Chen, Si; Zhou, Wenbin; Li, Jing; Huang, Qing; Xu, Tingting; Gao, Zhiyuan; Wang, Dongyu; Zhao, Shuo; Dong, Hao (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a common chronic, autoimmune-mediated inflammatory and neurodegenerative disease of the central nervous system. The treatment of MS has enormous progress with disease-modifying drugs, but the complexity of the disease course and the clinical symptoms of MS requires personalized treatment and disease management, including non-pharmacological treatment. Transcranial magnetic stimulation (TMS) is a painless and non-invasive brain stimulation technique, which has been widely used in neurological diseases. In this review, we mainly focus on the progress of physiological assessment and treatment of TMS in MS.